Codonopsis pilosula seedling drought- responsive key genes and pathways revealed by comparative transcriptome - Wang, Hongyan; Chen, Yuan; Liu, Lanlan; Guo, Fengxia; Liang, Wei; Dong, Linlin; Dong, Pengbin; Cheng, Jiali; Chen, Yongzhong (Frontiers in Plant Science, 2024)
Backgroud Codonopsis pilosula (Campanulaceae) is a traditional herbal plant that is widely used in China, and the drought stress during the seedling stage directly affects the quality, ultimately impacting its yield. However, the molecular mechanisms underlying the drought resistance of C. pilosula seedlings remain unclear. Method Herein, we conducted extensive comparative transcriptome and physiological studies on two distinct C. pilosula cultivars (G1 and W1) seedlings subjected to a four-day drought treatment. Results Our findings revealed that cultivar G1 exhibited enhanced retention of proline and chlorophyll, alongside a marked elevation in peroxidase activity, coupled with diminished levels of malondialdehyde and reduced leaf relative electrolyte leakage compared to the cultivar W1. This suggested cultivar G1 had relatively higher protective enzyme activity and ROS quenching capacity. We discerned a total of 21,535 expressed genes and identified 4,192 differentially expressed genes (DEGs) by RNA sequencing (RNA-seq). Our analysis revealed that 1,764 DEGs unique to G1 and these DEGs underwent thorough annotation and functional categorization utilizing diverse databases. Under drought conditions, the DEGs in G1 were predominantly linked to starch and sucrose metabolic pathways, plant hormone signaling, and glutathione metabolism. Notably, the drought-responsive genes in G1 were heavily implicated in hormonal modulation, such as ABA receptor3-like gene (PYL9), regulation by transcription factors (KAN4, BHLH80, ERF1B), and the orchestration of drought-responsive gene expression. These results suggest that cultivar G1 possesses stronger stress tolerance and can better adapt to drought growing conditions. The congruence between qRT-PCR validation and RNA-seq data for fifteen DEGs further substantiated our findings. Conclusion Our research provides novel insights into the physiological adaptations of C. pilosula to arid conditions and lays the groundwork for the development of new, drought-tolerant C. pilosula cultivars.